Adventist Young People's Perceptions of Missionaries in The Adventist Church Environment Seventh Day Based on Mark 10:29-30 - Langmau, Thomas Isak; Pane, Exson Eduaman (Kirana Publisher (KNPub), 2024)
This study explores the perceptions of young people in the Seventh-day Adventist Church regarding the missionary task and contribution. The main focus of this research is the Adventist young people's views on mission endeavors in relation to the teachings from Mark 10:29-30. To conduct this research, the methods used include qualitative methods, and analysis of scriptural texts. The results of this study show the different ways Adventist young people see the importance of missions, the difficulties missionaries face, and how the teachings from Mark 10:29-30 influence their perception of sacrifice and reward in the context of ecclesiastical missions. The findings may help to increase young people's understanding and participation in ecclesial mission activities.